Evaluation of Anxiety, Depression, and Stress in Parents During the COVID-19 Pandemic - Doğan, Melike Demir; Aksoy, Bahar (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: The COVID-19 pandemic and preventive measures, have caused uncontrollable lifestyle changes and impacted millions of children and parents. Objective: This study was conducted to determine the anxiety, stress and depression levels and the factors affecting them of the parents during the COVID-19 pandemic. Materials and Methods: This descriptive and cross-sectional study was conducted between July and October 2020. In the study, 237 people who can be reached from people who actively use internet-social media. Correlation, student’s t, and ANOVA tests were used for analysis. Results: Participants with family members with chronic illness had significantly higher stress, anxiety, and depression scores than those without family members with chronic illness. Participants with COVID-19 symptoms had significantly higher stress, anxiety, and depression scores than those without COVID-19 symptoms. Participants who had been hospitalized due to COVID-19 had significantly higher stress, anxiety, and depression scores than those who had not. Participants with family members or friends who died from COVID-19 had higher DASS-21 scores than those with no family members or friends who died from COVID-19 (p<0.01). There was a weak positive correlation between DASS- 21 scores and age and income (p<0.05). There was a strong positive correlation between DASS-21 scores and screen time (p<0.05). Conclusion: It was determined that among the participants who were quarantined due to COVID-19 or had COVID-disease in their family and had someone died very near and dear, and those with chronic diseases had higher levels of anxiety, stress and depression. International Journal of Human and Health Sciences Vol. 06 No. 01 January’22 Page: 67-74